Collaborative Model of Teachers, Students, and Families to Improve Parents Knowledge and Skills on Food Safety of Elementary School Students - Sigit Mulyono; Elly Nurachmah; Junaiti Sahar; Sabarinah Prasetyo (Jurnal Ners, 2018)
Introduction: School-age children in Indonesia are at risk of health problems due to food insecurity. Parents have a very important role in preparing safe food, both at home and for lunch at school. The aim of this study was to determine the effect of a collaboration model of teachers, students, and their families (KOGUSIGA) towards the parents’ knowledge and skills on the food safety of elementary school students.Methods: This study applied a quasi-experiment design pre- and post-test with a control group. The subject sample used was the total sampling method, involving 206 parents. The study was conducted for over 10 weeks, supported with modules for nurses and parents, textbooks for the students and their families, and a student workbook.Results: The results showed that the KOGUSIGA model is associated significantly with greater knowledge (p-value = 0.000; with a mean difference of 20.23) and the parent’s skills (p-value = 0.000; with a mean difference of 12.3) to do with food insecurity.Conclusions: The KOGUSIGA model tends to improve the knowledge and skills parents significantly, in relation to the food safety of the students. It is expected that the KOGUSIGA model will be applied under the community health nursing/school health nurses’ supervision.